STUDI PARAMETER REAKTOR BERBAHAN BAKAR UO2 DENGAN MODERATOR H2O DAN PENDINGIN H2O - Richardina, Very; Budi, Wahyu Setia; Tjiptono, Tri Wulan (BERKALA FISIKA, 2015)
Research about study of Pressurized Water Reactor (PWR) parameters using UO2 as fuel materials with moderator of H2O and coolant of H2O for heterogeneous infinite cylinder design  has realized. There is one of design to make nuclear reactor, it is a neutronic design. At neutronic design, first must calculations to determine group constants ( neutron cross section and the multiplication factor). The neutronic equations with one dimensional  transport theory for annulus geometry can be solved with WIMSD5B codes. Numeric method that used was one dimensional homogenization cell methods. To archieve   steady state or reactor, used enrichment of U235 between 2% until 3,2% with variation 0,05%. From the result with cluster methods with 32 groups and 10 regions, steady states of reactor at enrichment of U235 is 2,9% with effective multiplication factor (keff) = 1,006491. Keywords: PWR, reactor parameters, effective multiplication factor (keff), WIMSD5B